Power converters design and analysis for high power piezoelectric ultrasonic transducers - Davari, P.; Ghasemi, N.; Zare, Firuz (2014)
© 2014 IEEE. High power piezoelectric ultrasonic transducers have been widely exploited in a variety of applications. The critical behaviour of a piezoelectric device is encapsulated in its resonant frequencies because of its maximum transmission performance at these frequencies. Therefore power electronic converters should be tuned at those resonant frequencies to transfer electrical power to mechanical power efficiently. However, structural and environmental changes cause variations in the device resonant frequencies which can degrade the system performance. Hence, estimating the device resonant frequencies within the incorporated setup can significantly improve the system performance. This paper proposes an efficient resonant frequency estimation approach to maintain the performance of high power ultrasonic applications using the employed power converter. Experimental validations indicate the effectiveness of the proposed method.